2018
DOI: 10.1016/j.tem.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Obesogenic Endocrine Disrupting Chemicals: Identifying Knowledge Gaps

Abstract: Endocrine disrupting chemicals (EDCs) are compounds that are part of everyday consumer products and industrial manufacturing processes. EDCs can interfere with the endocrine system, including the adipose tissue. Accumulating evidence from epidemiological, animal, and in vitro studies demonstrates that EDCs can alter body weight, adipose tissue expansion, circulating lipid profile, and adipogenesis, with some resulting in transgenerational effects. These outcomes appear to be mediated through multiple mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 165 publications
(232 reference statements)
1
38
0
Order By: Relevance
“…These data fit within a broadening context of multigenerational and transgenerational effects of multiple EDC classes on various endocrine and metabolic tissues [7,[26][27][28][29]. Recently, studies have demonstrated that changes in the expression and methylation of imprinted genes in the brain persist across three generations after BPA exposure in mice [30].…”
Section: Exposures During Sensitive Developmental Windowssupporting
confidence: 58%
“…These data fit within a broadening context of multigenerational and transgenerational effects of multiple EDC classes on various endocrine and metabolic tissues [7,[26][27][28][29]. Recently, studies have demonstrated that changes in the expression and methylation of imprinted genes in the brain persist across three generations after BPA exposure in mice [30].…”
Section: Exposures During Sensitive Developmental Windowssupporting
confidence: 58%
“… 30 Thus, EDCs with estrogenic, antiandrogenic, or obesogenic actions may have differing associations with puberty in boys and girls. 27 , 31 , 32 To what extent EDCs contribute to the secular trend in male pubertal timing presented in this study is not clear. Our findings indicate that there is a robust secular trend for earlier pubertal timing in boys that is explained by other unknown factors than the obesity epidemic and demographic changes.…”
Section: Discussionmentioning
confidence: 88%
“…114 EDCs appear to work through a variety of mechanisms, including direct binding to hormone receptors, disrupting mitochondrial function, altering the intestinal microbiome, and modifying the epigenome. 115,116 Screening and Diagnosis…”
Section: Environmental Exposuresmentioning
confidence: 99%